Impact of Video-Based Error Correction Learning for Cardiopulmonary Resuscitation Training: Quasi-Experimental Study - Yun Wang; Junzuo Fu; Shaoping Wang; Huijuan Wang; Wei Gao; Lina Huang (JMIR Publications, 2024)
Abstract BackgroundVideo-based error correction (VBEC) in medical education could offer immediate feedback, promote enhanced learning retention, and foster reflective practice. However, its application in cardiopulmonary resuscitation (CPR) training has not been investigated. ObjectiveThe objective of this study is to assess whether the VBEC procedure could improve the training performance of CPR among anesthesiology residents. MethodsA quasi-experimental study was conducted among anesthesiology residents between December 2022 and April 2023. Primary outcomes included a posttraining knowledge test and practical assessment scores. Secondary outcomes included the number of residents who correctly conducted CPR at each step, the rate of common mistakes during the CPR process, and the self-assessment results. A total of 80 anesthesiology residents were divided into a VBEC group (n=40) and a control group (n=40). The VBEC group underwent a 15-minute VBEC CPR training, whereas the control group underwent a 15-minute video-prompting CPR training. ResultsThe posttraining knowledge test score of the VBEC group was significantly higher than that of the control group (73, SD 10.5 vs 65.1, SD 11.4; PPPPP ConclusionsVBEC may be a promising strategy compared to video prompting for CPR training among anesthesiology residents.